(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In this work the total ground state energy per atom for Fullerenes (C60), Graphite and Diamond were computed using Density Functional Theory (DFT) code FHI-aims (Fritz Haber Institute- ab initio molecular simulations). The density functionals used are the local-density approximation (LDA) in the parameterization by Perdew and Wang 1992, Perdew and Zunger 1981, the generalized gradient functional PBE, and PBE+vdW approach as defined by Tkatchenko and Scheffler. The results obtained from the computations of the ground state energies of diamond, fullerenes and graphite were -1028.51549311 eV, -1027.194 eV and -1035.469 eV, respectively. These results agree with both experimental and theoretical results regardless of the exchange and correlation functionals used.